1964
DOI: 10.1192/bjp.110.465.146
|View full text |Cite
|
Sign up to set email alerts
|

Old Age Mental Disorders in Newcastle upon Tyne

Abstract: Community surveys abroad have shown that there is a high prevalence of serious mental illness in old age, much of which is not treated in hospital (Gruenberg, 1961; Nielsen, 1963). Most community surveys of the aged in this country have, however, been concerned chiefly with general medical and social problems (Sheldon, 1948; Simonds and Stewart, 1954), or have formed part of whole-population studies and recorded only the most severe kinds of mental disturbance in old age (Mayer-Gross, 1948). An exception is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
171
3
3

Year Published

1974
1974
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 527 publications
(185 citation statements)
references
References 7 publications
8
171
3
3
Order By: Relevance
“…This comorbidity was already noted by Kay et al,90 who found that most affective disorders in the elderly were an admixture of depressive and anxiety symptoms. Lindesay et al 27 reported that 91% of the elderly with general anxiety in the population also had depression, and Blanchard et al 42 reported that 95% of those with depression had symptoms of anxiety.…”
Section: Comorbiditymentioning
confidence: 73%
“…This comorbidity was already noted by Kay et al,90 who found that most affective disorders in the elderly were an admixture of depressive and anxiety symptoms. Lindesay et al 27 reported that 91% of the elderly with general anxiety in the population also had depression, and Blanchard et al 42 reported that 95% of those with depression had symptoms of anxiety.…”
Section: Comorbiditymentioning
confidence: 73%
“…Old-age psychiatry arose in response to the epidemiological imperative of dementia (Kay et al 1964). While late-onset schizophrenia and depression have been the subject of research interest since, the neurotic disorders, in particular somatoform disorders, have tended to be relatively neglected (Jorm, 1998).…”
mentioning
confidence: 99%
“…Organic Brain Syndrome (OBS) was defined according to Kay et al 14 who sub-divided the OBS-cases into two groups: mild cases were those showing mental deterioration in excess of that expected at the subjects' but without obvious clinical dementia, and corresponded to OSR of 1 or 2 in the Clinical Interview Schedule; and moderate-severe cases were those in which clinical dementia was present and included senile dementia multi-infarct dementias and other organic syndromes. The OSR was respectively 3 or 4.…”
Section: Methodsmentioning
confidence: 99%